2020
DOI: 10.3847/1538-4357/ab98fd
|View full text |Cite
|
Sign up to set email alerts
|

New Constraints on the Origin of Surface Brightness Profile Breaks of Disk Galaxies from MaNGA

Abstract: In an effort to probe the origin of surface brightness profile (SBP) breaks widely observed in nearby disk galaxies, we carry out a comparative study of stellar population profiles of 635 disk galaxies selected from the Mapping Nearby Galaxies at Apache Point Observatory spectroscopic survey. We classify our galaxies into single exponential (Ti), down-bending (Tii), and up-bending (Tiii) SBP types and derive their spin parameters and radial profiles of age/metallicity-sensitive spectral features. Most Tii (Tii… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 67 publications
8
14
1
Order By: Relevance
“…Kennicutt 1989;Schaye 2004), and simulations of disc galaxies have found that the break may be a result of a star formation cutoff associated with a drop in cold gas density (Roškar et al 2008;Martínez-Serrano et al 2009;Sánchez-Blázquez et al 2009). This picture is consistent with the down-bending star-formation rate (SFR) profiles of Type II galaxies (Tang et al 2020). The radial position of the break has also been found to increase with cosmic time (Trujillo & Pohlen 2005;Azzollini et al 2008b) and galaxy mass (Pohlen & Trujillo 2006;Muñoz-Mateos et al 2013), consistent with inside-out growth of disc galaxies.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…Kennicutt 1989;Schaye 2004), and simulations of disc galaxies have found that the break may be a result of a star formation cutoff associated with a drop in cold gas density (Roškar et al 2008;Martínez-Serrano et al 2009;Sánchez-Blázquez et al 2009). This picture is consistent with the down-bending star-formation rate (SFR) profiles of Type II galaxies (Tang et al 2020). The radial position of the break has also been found to increase with cosmic time (Trujillo & Pohlen 2005;Azzollini et al 2008b) and galaxy mass (Pohlen & Trujillo 2006;Muñoz-Mateos et al 2013), consistent with inside-out growth of disc galaxies.…”
Section: Introductionsupporting
confidence: 80%
“…In Type II (truncated) galaxies, the break in the exponential light ★ E-mail: joel.pfeffer@icrar.org profile has been observed to coincide with a minimum in the colour, age and mass-to-light ratio profiles (Azzollini et al 2008a;Bakos et al 2008;Zheng et al 2015;Ruiz-Lara et al 2016). The breaks are largely absent in the mass profiles of Type II galaxies (Bakos et al 2008;Tang et al 2020) and are thus related to radial gradients in the stellar populations (similarly found in the simulations of Sánchez-Blázquez et al 2009). The disc breaks may result from star formation thresholds in the outer parts of galaxies (e.g.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations